MENINGKATKAN KEMAMPUAN OPERASI PERKALIAN UNTUK ANAK DISKALKULIA MELALUI METODE GARISMATIKA - Elisa Arisandi (Jurnal Penelitian Pendidikan Khusus, 2014)
ABSTRACT This research was conducted as there was a problem signifying that a child with dyscalculia in the fourth grade of SD Negeri 09 Koto Luar Kec. Pauh Padang got difficulties in doing multiplication. To deal with this condition, this research was aimed at testing whether the use garismatika methods could improve multiplication ability of the student with dyscalculia in the fourth grade of SD Negeri 09 Koto Luar Kec. Pauh Padang. Kata Kunci: Anak Diskalkulia ; Operasi Perkalian; Metode Garismatika.